Non-profit organizations of Tuva as subjects of demographic policy implementation - Volkova, Olga A.; Osadchaya, Galina I. (The New Research of Tuva, 2023)
The article discusses the issue of the use of potential of non-profit organizations as subjects of demographic policy implementation drawing on the example of the Republic of Tuva.There were 82 socially oriented non-profit organizations in Tuva at the end of 2022 (15% of the total number of NGOs). Their activities are aimed at solving social problems and developing civil society in the region. They are also to a different extent related to the implementation of the demographic policy of the Russian Federation. In accordance with the objectives of the state demographic policy of Russia the identified NGOs are classified as contributing to reduce premature mortality of Russian citizens, to promote the health of residents of Russian regions, to increase the birth rate in the country, to strengthen the traditional family, to preserve spiritual and moral values and to provide social integration of migrants. The authors note some specific names of NGOs that correspond to certain tasks and that have already been supported by grants, first of all by the Presidential Grants Fund.
Keywords: demographic security; demographic policy; non-profit organization; Tuva; Republic of Tuva